2000
DOI: 10.1159/000055911
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-Mediated in vitro Invasion of Human Glioma Cells through Extracellular-Signal-Regulated Kinase and Ornithine Decarboxylase

Abstract: We investigated the involvement of protein kinase C (PKC) in the in vitro invasiveness of the A-172, U-87 and U-373 human glioma cell lines, as well as the role of ornithine decarboxylase (ODC) and/or extracellular-signal-regulated kinase (ERK) in the actions of PKC. Thus, cells were treated under serum-free conditions with the PKC activator phorbol 12-myristate 13-acetate (PMA), or with the PKC inhibitors bisindolylmaleimide I (GF 109203X) or calphostin C in the absence or presence of the ODC inhibitor D,L-α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 42 publications
1
9
1
Order By: Relevance
“…Our PKC data lent credence to the hypothesis that claudin-1 might be involved in melanoma malignancy, as PKC is known to be important for melanoma metastasis, and our laboratory as well as others, have shown that mechanisms which upregulate PKC can result in increases in melanoma cell motility (Weeraratna et al, 2002). In addition, PKC activation can increase levels of MMPs, via the p38MAPK pathway (da Rocha et al, 2000;Park et al, 2003). Further data from our laboratory support this observation, showing that the activation of conventional PKCs using phorbol ester results not only in the increase of claudin-1, but also in the increase of MMP-2 secretion (data not shown).…”
Section: Discussionsupporting
confidence: 77%
“…Our PKC data lent credence to the hypothesis that claudin-1 might be involved in melanoma malignancy, as PKC is known to be important for melanoma metastasis, and our laboratory as well as others, have shown that mechanisms which upregulate PKC can result in increases in melanoma cell motility (Weeraratna et al, 2002). In addition, PKC activation can increase levels of MMPs, via the p38MAPK pathway (da Rocha et al, 2000;Park et al, 2003). Further data from our laboratory support this observation, showing that the activation of conventional PKCs using phorbol ester results not only in the increase of claudin-1, but also in the increase of MMP-2 secretion (data not shown).…”
Section: Discussionsupporting
confidence: 77%
“…Among these is the gene for ornithine decarboxylase (ODC) [68], the rate-limiting enzyme in the biosynthesis of spermine, spermidine, and putrescine [69]. These polyamines have been implicated in cell transformation [70,71], the accelerated G 1 -to-S phase passage of cancer cells [72], as well as processes related to excessive extracellular matrix degradation [68,73,74].…”
Section: Participation Of Pkc In Signal Transduction Pathwaysmentioning
confidence: 99%
“…This could account for the increased ODC mRNA expression and enzyme activity, as well as the progression to malignancy, unchecked S phase transition, growth factor independence, protection against apoptosis, and invasive behavior seen in both non-glioma-and glioma-derived cell lines containing amplified EGF receptor [73][74][75], constitutively active Ras [72], hyperactivated ERK [74,75], and/or overexpressed PKC [69,76,77]. These observations are in accordance with a significant contribution of PKC in well-established signaling pathways for glioma cell proliferation and invasion.…”
Section: Participation Of Pkc In Signal Transduction Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of invasive cells in rAd-ODC/Ex3as-treated group was 19.478.79, which was far less than that of other groups. As LNCap cell line in essence has little invasion, the Matrigel assay was only carried out in PC-3 32 Similarly, the work of Manni et al 33 supported a role of polyamines in promoting breast cancer aggressiveness, particularly with regard to the development of distant metastasis.…”
Section: Discussionmentioning
confidence: 99%